Perdagangan Bebas Dalam Pandangan Islam - Mirsa Astuti (Iuris Studia: Jurnal Kajian Hukum, 2022)
The meaning of free trade is actually the reduction or elimination of trade barriers, both tariffs (exports and imports) and non-tariffs. Free trade activities carried out by a country with other countries bring benefits, namely being able to enjoy products not only from products made in the country itself, but also being able to consume products made abroad easily because with the free trade, imported goods can enter freely. into the country. In addition, there is an increasingly open international relationship between countries. In the view of Islam, free trade is not trade that is as free as possible, but trade that tries to optimize trade relations with foreign countries on the one hand and prohibits trade in certain commodities that interfere with the benefit of the Muslims on the other. save mankind. In reality, these activities occur between two parties, namely the seller and the buyer for certain commodities. Thus, the pillars of trade are traders, not commodities. The criteria for free trade according to the Islamic view are responsible, ethical, right, fair and balanced. Islam stipulates regarding trade the benchmarks are honesty, trust and sincerity. These trading principles have been regulated in the Qur'an and Sunnah. This research is descriptive-analytic with the approach used is normative juridical. The collected data is then processed and analyzed qualitatively, using the inductive method to draw a conclusion.